AUTHORITIES OF CIVIL SERVANT INVESTIGATES IN CONDUCTING INVESTIGATIONS ON ACTS OF CORPORATE MALADMINISTRATION IN TELECOMMUNICATIONS ACCORDING TO LAW NO. 36 OF 1999 CONCERNING TELECOMMUNICATIONS ADJUSTED TO THE PRINCIPLE OF LEGAL CERTAINTY - Abdul Hayy Nasution; Edi Setiadi; Yeti Sumiati (International Journal of Social Science, 2023)
This research was conducted to find out how the laws and regulations regulate PPNS Authority in conducting investigations of corporate maladministration in the telecommunications sector, then regarding the Implementation of PPNS Authority in conducting investigations or corporate maladministration actions in the field of telecommunications, and find out how the PPNS authority mechanism to conduct maladministration investigations telecommunications sector corporations on the principle of legal certainty. This study uses a normative juridical approach, namely by examining theories, concepts, legal principles and laws and regulations and using the preparation of analytical descriptive research specifications, and the data used are primary, secondary, and tertiary. The results of this study are that PPNS is obliged to notify the investigation to Polri investigators. in the form of tactical assistance, technical assistance, coercive assistance and investigative consulting assistance. The case files must be submitted to the Prosecutor, in accordance with Article 110 paragraph (1) of the Criminal Procedure Code, the submission is carried out through Polri investigators in accordance with Article 107 paragraph (3) of the Criminal Procedure Code